A study of implicatures in conversations in the film “slumdog millionaire” - TRẦN, HỒ YÊN VINH (2016)
This study aimed to study the conversational implicatures in the film “Slumdog millionaire”. It was done with a discourse analysis and pragmatics. The researcher is interested in watching the film “Slumdog millionaire” and identifies conversational implicature found in the utterances of the characters in the film. After analyzing, the researcher found out the types of conversational implicature and the motivation of producing them. The researcher used Grice’s theory of conversational implicature as the basis of the analysis of the study. The utterances containing implicatures fall into two types: generalized conversational implicatures and particularized conversational implicatures. The study reveals that one single utterance can have two types of conversational implicature. In addition, the researcher realized that the theory of an indefinite article of the type “a/an X”, typically interpreted according to the generalized conversational implicature that: a/an X +> not speaker’s X cannot be always right in this study because it can be interpreted as the speaker’s X. Moreover, the researcher found out the motivation of producing conversational implicatures is manufactured by the nine reasons: to express the feeling, to stress the statement , to clarify the idea, to warn someone, to be sarcastic, to inform something, to give someone advice, to make a request and to make an obligation. Those findings also proved that not all the communication was successful. This means that the hearer must manage to get involved in interaction in order to understand what the speaker wants to convey.